Denovo variants in POGZ and YY1 genes: The novel mega players for neurodevelopmental syndromes in two unrelated consanguineous families - Behjat Ul Mudassir; Mujaddid Mudassir; Jamal B. Williams; Zehra Agha (PLoS ONE, 2025)
Novel denovo variants of exome sequences are major cause of pathogenic neurodevelopmental disorders with a dominant genetic mechanism that emphasize their heterogeneity and complex phenotypes. White Sutton syndrome and Gabriele-de-Vries syndrome are congenital neuro-impairments with overlap of severe intellectual disability, microcephaly, convulsions, seizures, delayed development, dysmorphism of faces, retinal diseases, movement disorders and autistic traits. POGZ gene codes for pogo transposable element-derived zinc-finger protein and YY1 gene regulates transcription, chromatin, and RNA-binding proteins that have been associated with White Sutton and Gabriele-de-Vries syndromes, in recent data. We present probands of two unrelated consanguineous families with complicated, unexplained neurocognitive syndromic characteristics clinically undiagnosed. Objectives of the study were to identify altered genetics and protein characteristics underlying molecular pathological pathways in both the patients. Whole exome sequencing identifies novel, denovo missense variant NM_015100.4: c.776 C>T (p. Pro259Leu) in exons 19 of POGZ gene and non-frameshift variant NM_003403.5: c.141_143delGGA (p. Glu47del) in exon 1 of YY1 gene for White Sutton syndrome in eight years five-month-old girl and Gabriele-de-Vries syndrome in seven years eight months old boy residing in Rawalpindi and Chakwal districts of Punjab, Pakistan respectively. Protein modelling for identified variants predicts size and conformation modifications in mutated amino acid residues that lead to damaging effects in the conserved domains expressed as neurological pathophysiology. The present study widens the diversely ethnic and highly inbred gene pool of Punjab, Pakistan population for spontaneously originated deleterious mutations and contributes to the continuously expanding phenotypic canvas. Molecular genetic identification and personalized diagnosis for the patients suffering from complicated neurodevelopmental phenotypes, for better care, management of day-to-day activities and prolonged life span are the utmost hopes.